Biodiversity of Plant Growth Promoting Rhizobacteria In Mangrove Ecosystem - A Review - Shakilabanu, S. (International Journal of Pharmaceutical & Biological Archive, 2012)
Biodiversity of Plant Growth Promoting Rhizobacteria In Mangrove Ecosystem - A Review